2016
DOI: 10.1111/pace.12959
|View full text |Cite
|
Sign up to set email alerts
|

CTA Detection of Left Atrial Stasis and Thrombus in Patients with Atrial Fibrillation

Abstract: We reviewed CTA and transesophageal echocardiographic images obtained in 861 consecutive patients with a history of AF undergoing same-day CTA and transesophageal echocardiogram (TEE) before AF ablation at a single hospital (2006-2013). CTA findings of LAA filling defects from acquisitions without electrocardiogram gating were compared to TEE features of LAA stasis (grade 0-4) and thrombus. Stasis grade 0 or 1 by TEE in the absence of thrombus was defined as a negative result. In addition, LAA peak flow veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…The results of the safety analysis in our study shows that the use of CCTA only with delayed imaging protocol is enough to rule out a LAAT in patients who are at low to intermediate risk of stroke related to AF. This is in agreement with prior studies such as the one conducted by Wang et al . which showed that among 670 CCTA‐negative patients for LAAT or stasis, 669 (99%) were negative by TEE with one false‐negative CCTA in a patient with grade 2 stasis by TEE but no thrombus, yielding a NPV of 99.9%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the safety analysis in our study shows that the use of CCTA only with delayed imaging protocol is enough to rule out a LAAT in patients who are at low to intermediate risk of stroke related to AF. This is in agreement with prior studies such as the one conducted by Wang et al . which showed that among 670 CCTA‐negative patients for LAAT or stasis, 669 (99%) were negative by TEE with one false‐negative CCTA in a patient with grade 2 stasis by TEE but no thrombus, yielding a NPV of 99.9%.…”
Section: Discussionsupporting
confidence: 92%
“…However, we were not able to show a significant cost difference when TEE was eliminated from the preprocedural imaging protocol. The CCTA results are consistent with prior literature which shows that the sole use CCTA with delayed imaging is a safe and effective method in ruling out a LAAT, potentially obviating the need for TEE prior to AFA procedure . Prior literature showed that, when using confirmatory intracardiac echocardiography as the reference standard, the use of CCTA‐alone with delayed imaging protocol had a 100% PPV, 100% NPV, 100% sensitivity, and a 100% specificity (when equivocal results were considered negative) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…10 Enlargement of the cardiac chambers causes stasis of blood and an increased risk of thrombus formation in the left atrial appendage and the left atrium itself. 11 Our patient, with a history of cardiomy-opathy and mitral regurgitation, had this risk. One paper suggests that chronic mitral regurgitation can cause a rare type C calcification in the posterior wall of the left atrium.…”
Section: Discussionmentioning
confidence: 71%
“…Although the detection of thrombi using contrast CT exhibits excellent negative predictive values (99-100%), the positive predictive value is still low, at 13-31%. [14][15][16] This may be attributed predominantly to difficulties in distinguishing real thrombi from circulatory stasis in the LAA, particularly at a low blood velocity. The discrimination between thrombi and circulatory stasis is more crucial in patients with persistent or longstanding AF than in those with paroxysmal AF; in the former population, 28% of patients showed CDs on sCT in the early phase and as a reference of TEE or ICE, the positive and negative predictive values were 40.7% and 100%, respectively.…”
Section: Cds Observed On Late-pctmentioning
confidence: 99%